A tissue-adhesive hydrogel and methods of making and using the same

The tissue-adhesive hydrogel formed by injection utilizes a mixture of aminated polymers and coupling agents to solve the adhesion problem in humid and dynamic environments, achieving rapid and effective tissue adhesion and wound healing.

CN113087934BActive Publication Date: 2026-11-06EAST CHINA UNIV OF SCI & TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202110425402.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-04-20
Publication Date
2026-11-06
Estimated Expiration
2041-04-20

AI Technical Summary

Technical Problem

Existing tissue adhesive materials have poor adhesion in humid and dynamic physiological environments, and traditional suturing and stapled methods cause secondary damage to tissues, are difficult to operate, and cannot adapt to complex and ever-changing battlefield environments.

Method used

A tissue-adhesive hydrogel formed by injection was developed, which utilizes polymers such as aminated polyethylene glycol-polyglycerol sebacic acid and chitosan-gallic acid mixed with a coupling agent to form a hydrogel with excellent viscoelasticity, capable of bonding in humid and dynamic environments.

Benefits of technology

It achieves rapid adhesion in humid and dynamic physiological environments, with good adhesive strength and biocompatibility, and can in situ adhere irregular wounds in a short time, promoting wound healing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure QLYQS_1
    Figure QLYQS_1
  • Figure QLYQS_4
    Figure QLYQS_4
  • Figure QLYQS_5
    Figure QLYQS_5
Patent Text Reader

Abstract

The application provides a hydrogel. Specifically, the application provides a tissue-adhesive hydrogel suitable for moist and dynamic physiological environments, which is formed by mixing a hydrogel precursor solution with a coupling agent; wherein the hydrogel precursor solution comprises a first polymer, a second polymer and a third polymer; the first polymer is an aminated polyethylene glycol-polyglycerol sebacate; the side chain of the second polymer comprises an amino group and a polyphenol structure; and the side chain of the third polymer comprises a carboxyl group. The hydrogel of the application has excellent mechanical strength, rheological properties and compression properties, and has excellent adhesive strength and cyclic performance for moist tissues and dynamic environments.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the fields of materials science and clinical medicine, specifically to a tissue-adhesive hydrogel that can be formed by injection and is adaptable to humid and dynamic physiological environments, as well as its preparation method and applications. Background Technology

[0002] The modern battlefield demands a massive amount of tissue adhesives, and highly efficient tissue adhesives are crucial for reducing battlefield casualties. Simultaneously, there is an urgent need in clinical surgery for tissue adhesives that can replace traditional sutures or staples to simplify complex surgical procedures. Currently, surgical incisions or accidental injuries are primarily closed using traditional suturing or stapled methods. However, suturing and stapled methods can cause secondary damage to tissues, have poor sealing effects, are difficult to perform, and are unsuitable for the complex and ever-changing battlefield environment. Existing commercially available and clinically widely used tissue adhesives mainly include fibrin glue and cyanoacrylates. However, fibrin glue has weak bonding strength and is expensive, while cyanoacrylate tissue adhesives suffer from drawbacks such as hardening after curing and toxic degradation products. Furthermore, both methods are ineffective in humid and dynamic physiological environments.

[0003] Hydrogels with a certain degree of viscoelasticity contain a large amount of water, and their structure and properties are closer to those of natural soft tissue. They are widely used in the field of tissue adhesion, and their inherent viscoelasticity allows them to better adapt to dynamic environments. Furthermore, to address the higher demands placed on tissue adhesion by moist and dynamic physiological environments, it is also essential to enhance their adhesive performance in both moist and dynamic physiological environments.

[0004] Therefore, the development of tissue-adhesive hydrogels that are easy to use and can adapt to humid and dynamic physiological environments through injection has significant practical application value in modern battlefields and clinical settings. Summary of the Invention

[0005] The purpose of this invention is to provide a tissue adhesive hydrogel that can be rapidly gelled by injection and adaptable to humid and dynamic physiological environments.

[0006] In a first aspect of the present invention, a tissue-adhesive hydrogel is provided, characterized in that the tissue-adhesive hydrogel is formed by coupling a hydrogel precursor solution with a coupling agent;

[0007] The hydrogel precursor solution comprises a first polymer, a second polymer, and a third polymer.

[0008] In another preferred embodiment, the first polymer and the third polymer are covalently bonded by amide bonds, and the second polymer and the third polymer are covalently bonded by amide bonds.

[0009] In another preferred embodiment, the first polymer, the second polymer, and the third polymer are all non-toxic polymers that can be directly contacted by the human body.

[0010] In another preferred embodiment, the first polymer is the main matrix material.

[0011] In another preferred embodiment, the first polymer is obtained by amylation modification of a precursor polymer of the first polymer.

[0012] In another preferred embodiment, the precursor polymer of the first polymer is polyethylene glycol-polyglycerol sebacic acid, containing structural units as shown in Formula III:

[0013]

[0014] Where c is 1-20 and d is 5-60.

[0015] In another preferred embodiment, the first polymer is obtained by replacing the H of the hydroxyl group in the side chain of the precursor polymer of the first polymer with an amino-modifying substance.

[0016] In another preferred embodiment, the first polymer is an aminated polyethylene glycol-polyglycerol sebacate, which contains structural units as shown in Formula I:

[0017]

[0018] In the formula,

[0019] a is 1-20, b is 5-60;

[0020] Y is independently selected from the following groups: H, Furthermore, on average, each structural unit contains at least one

[0021] This refers to the amino group being attached to the first polymer through a grafted chain structure.

[0022] In another preferred embodiment, the first polymer contains structural units as shown in Formula IV:

[0023]

[0024] In the formula,

[0025] a1 is 1-20, b1 is 5-60;

[0026] Z is independently selected from the following groups: H, Furthermore, each structural unit contains, on average, at least 1 to 1.4 Preferably, it contains at least 1.5 to 1.6 Preferably, it should contain at least 1.8

[0027] In another preferred embodiment, the first polymer has one or more of the following characteristics:

[0028] (a) The number average molecular weight is 5,000-50,000 Da, preferably 8,000-30,000 Da, and even more preferably 8,000-12,000 Da;

[0029] (b) The molecular weight distribution coefficient is 1.0 to 1.60, preferably 1.20 to 1.50;

[0030] (c) On average, a structural unit contains at least 1.4 Preferably containing at least 1.6 Preferably, it should contain at least 1.8

[0031] In another preferred embodiment, the amino grafting rate of the first polymer, i.e. the ratio of H of the original hydroxyl groups in the amino-substituted polyethylene glycol-polysaccharide glycerol, is greater than 70%, more preferably greater than 80%, and more preferably greater than 90%.

[0032] In another preferred embodiment, the method for preparing the first polymer includes the following steps:

[0033] (a1) Sebacic acid and tetrabutylammonium hydroxide were added to 95% ethanol at a molar ratio of 1:2, and the mixture was stirred at 55°C for 30 min. The ethanol and water were removed to obtain the product.

[0034] (b1) Under a nitrogen atmosphere, sebacic acid, polyethylene glycol diglycidyl ether (PEGDGE) and the product obtained in step (a1) were dissolved in anhydrous N,N-dimethylformamide in a molar ratio of 1:1:0.006 and stirred at 100°C for 72 h.

[0035] (c1) Dialysis purification of the mixture obtained in step (b) yields purified linear polyester polyethylene glycol-polyglycerol sebacate;

[0036] (d1) Under a nitrogen atmosphere, the linear polyester polyethylene glycol-polyglycerol sebacate (based on the amount of hydroxyl groups) obtained in step (c1), N-(tert-butoxycarbonyl)aminoacetic acid (BOC-glycine), N,N'-diisopropylcarbodiimide (DIC) and 4-dimethylaminopyridine (DMAP) were dissolved in anhydrous dichloromethane in a molar ratio of 1:1.2:2:0.05 and stirred at room temperature for 24 h.

[0037] (e1) The reaction mixture obtained in step (d1) is filtered, concentrated, and then the tert-butyloxycarbonyl group is removed by trifluoroacetic acid. After dialysis purification, the first polymer is obtained.

[0038] In another preferred embodiment, the side chains of the second polymer comprise amino groups and...

[0039] In another preferred embodiment, the second polymer is derived from a precursor polymer containing an amino group through... It was obtained through modification.

[0040] In another preferred embodiment, the precursor polymer of the second polymer containing amino groups is obtained through... Random copolymers formed by unit polymerization.

[0041] In another preferred embodiment, the precursor polymer of the second polymer containing amino groups is chitosan and its derivatives.

[0042] In another preferred embodiment, the described for

[0043] In another preferred embodiment, the described The grafting rate, that is, the proportion of H in the original amino group that is replaced by this group, is 5% to 30%.

[0044] In another preferred embodiment, the described The grafting rate, i.e., the proportion of H in the original amino group that is replaced by this group, is 8% to 20%, more preferably 8% to 12%.

[0045] In another preferred embodiment, the number-average molecular weight of the second polymer is 100-150 kDa.

[0046] In another preferred embodiment, the second polymer comprises a structure as shown in Formula II:

[0047]

[0048] Among them, the three monomers can be combined arbitrarily to obtain random copolymers;

[0049] l is 45%–80%, m is 5%–30%, and n is 15%–25%. The calculation method for l, m, and n is the corresponding number of repeating units divided by the total number of repeating units.

[0050] In another preferred embodiment, m in the polymer of formula II is 8% to 12%.

[0051] In another preferred embodiment, the second polymer is used for modification The substances are selected from the following group: gallic acid, myricetin, or combinations thereof.

[0052] In another preferred embodiment, the second polymer is gallic acid-grafted chitosan (chitosan-gallic acid), comprising the structure shown in Formula V:

[0053]

[0054] Among them, the three monomers can be combined arbitrarily to obtain random copolymers;

[0055] l1 is 45%–80%, m1 is 5%–30%, and n1 is 15%–25%. l1, m1, and n1 are calculated by dividing the corresponding number of repeating units by the total number of repeating units.

[0056] In another preferred embodiment, the gallic acid grafting rate of the chitosan-gallic acid, i.e., the proportion of gallic acid replacing H in the original amino group of chitosan, is 8% to 12%.

[0057] In another preferred embodiment, the method for preparing the second polymer includes:

[0058] Chitosan, EDC, NHS, and modifying substances were mixed in a protective gas atmosphere and in the presence of a solvent, and then post-treated to obtain the second polymer.

[0059] In another preferred embodiment, the method for preparing the second polymer includes the following steps:

[0060] (a2) Dissolve chitosan in 1M hydrochloric acid solution and adjust the pH to 5.5 with 2M sodium hydroxide solution;

[0061] (b2) Under an argon atmosphere, the modifier, EDC, and NHS are added dropwise to the chitosan solution in step (a2) in a molar ratio of 1.1:1.5:1.5:1 to the second polymer solution in step (a2), and the pH of the reaction system is maintained at 4.5-7.0, preferably 5.0-6.5, and more preferably 5.3-5.8. The mixture is continuously stirred during the addition process, and the reaction is continued for 12 hours after the addition is completed.

[0062] (c2) The product of step (b2) is purified by dialysis to obtain the second polymer.

[0063] In another preferred embodiment, the dripping rate in step (b2) is 0.5-2 drops / second, more preferably 0.5-1 drops / second.

[0064] In another preferred embodiment, step (b2) is performed in an ice bath at a temperature of -10-5°C, more preferably -5-0°C.

[0065] In another preferred embodiment, the side chain of the third polymer contains a carboxyl group.

[0066] In another preferred embodiment, the number-average molecular weight of the third polymer is 200-800 kDa.

[0067] In another preferred embodiment, the third polymer is selected from the group consisting of γ-polyglutamic acid, polyaspartic acid, or combinations thereof.

[0068] In another preferred embodiment, the third polymer is γ-polyglutamic acid.

[0069] In another preferred embodiment, the mass ratio of the first polymer to the second polymer is 5 to 50:1; and / or

[0070] The mass ratio of the first polymer to the third polymer is 1 to 8:1; and / or

[0071] The mass ratio of the second polymer to the third polymer is 1:1 to 10.

[0072] In another preferred embodiment, the mass ratio of the first polymer to the second polymer is 5–30:1, more preferably 5–20:1; and / or

[0073] The mass ratio of the first polymer to the third polymer is 1 to 5:1, more preferably 1 to 3:1; and / or

[0074] The mass ratio of the second polymer to the third polymer is 1:1 to 8, more preferably 1:1 to 5.

[0075] In another preferred embodiment, the concentration of the first polymer is 10-40% by mass-volume percentage of solute (g) / solvent (mL); the concentration of the second polymer is 0.5-4%; and the concentration of γ-polyglutamic acid is 5-15%.

[0076] In another preferred embodiment, the concentration of the first polymer is 20% by mass-volume percentage of solute (g) / solvent (mL); the concentration of the second polymer is 2%; and the concentration of the third polymer is 10%.

[0077] In another preferred embodiment, the solvent of the hydrogel precursor solution is selected from the group consisting of ultrapure water, PBS solution (pH=7.2), or combinations thereof.

[0078] In another preferred embodiment, the viscosity of the hydrogel precursor solution is 70-100 mPa·s.

[0079] In another preferred embodiment, the coupling agent comprises 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride (EDC) and N-hydroxysuccinimide (NHS).

[0080] In another preferred embodiment, the molar ratio of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride to N-hydroxysuccinimide is 0.6 to 2:1, preferably 0.8 to 1.2:1, and more preferably 1:1.

[0081] In another preferred embodiment, the concentration of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride in the coupling agent is 0.4 to 0.7 g / mL.

[0082] In another preferred embodiment, the molar ratio of the carboxyl group in the third polymer to the EDC in the coupling agent is 5 to 30:1.

[0083] In another preferred embodiment, the molar ratio of the carboxyl group in the third polymer to the EDC in the coupling agent is 10 to 25:1, for example 15:1 or 20:1, preferably 15:1.

[0084] In another preferred embodiment, the solvent of the coupling agent is selected from the group consisting of: ultrapure water, PBS buffer solution (pH=7.2).

[0085] In another preferred embodiment, the viscosity of the coupling agent is 0.6-0.8 mPa·s.

[0086] In another preferred embodiment, the hydrogel exhibits excellent tissue adhesion in moist and dynamic physiological environments.

[0087] In another preferred embodiment, the hydrogel has one or more of the following characteristics:

[0088] (1) The compressive strength at 80% compressive strain is 20-100 kPa;

[0089] (2) It recovers 100% after compression and release, and the hydrogel shows no significant loss after cyclic compression;

[0090] (3) The elongation at break reaches 200%-450%, more preferably 250%-420%;

[0091] (4) The lap-shear bond strength for moist tissue is 10-60 kPa, more preferably 12-48 kPa;

[0092] (5) The bonded damp tissue does not fall off after bending, stretching and twisting.

[0093] In a second aspect of the present invention, a method for preparing the hydrogel described in the first aspect of the present invention is provided, the method comprising: in the presence of a coupling agent, causing the hydrogel precursor solution described in the first aspect of the present invention to undergo a coupling reaction, thereby forming the hydrogel.

[0094] In another preferred embodiment, the preparation method includes the following steps:

[0095] (a) Providing a hydrogel precursor solution according to the first aspect of the present invention: the hydrogel precursor solution comprises a first polymer, a second polymer, and a third polymer;

[0096] (b) Providing a coupling agent solution according to the first aspect of the invention: the coupling agent comprises 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride (EDC) and N-hydroxysuccinimide (NHS);

[0097] (c) The hydrogel precursor solution is mixed with the coupling agent to obtain the hydrogel;

[0098] In another preferred embodiment, the solvents for the hydrogel precursor solution and the coupling agent solution are selected from the group consisting of water and / or PBS solution.

[0099] In another preferred embodiment, step (a) includes:

[0100] (a1) The first polymer, the second polymer, and the third polymer are dispersed in a solvent to obtain a solution of the first polymer, a solution of the second polymer, and a solution of the third polymer;

[0101] (a2) The first polymer solution and the second polymer solution are added dropwise to the third polymer solution to obtain the hydrogel precursor solution.

[0102] In another preferred embodiment, step (c) includes: transferring the mixture of the precursor solution and the coupling agent into a syringe and injecting it to form the hydrogel.

[0103] In another preferred embodiment, the solvent in step (a1) is selected from the group consisting of water and PBS buffer solution (pH=7.2).

[0104] In a third aspect of the invention, a precursor solution is provided for preparing the hydrogel described in the first aspect of the invention, the precursor solution comprising the first polymer, the second polymer, and the third polymer described in the first aspect of the invention.

[0105] In another preferred embodiment, the method for preparing the precursor solution that can be used to prepare the hydrogel includes the following steps:

[0106] (a) The first polymer, the second polymer, and the third polymer are dispersed in a solvent to obtain a first polymer solution, a second polymer solution, and a third polymer solution;

[0107] (b) The first polymer solution and the second polymer solution are added dropwise to the third polymer solution to obtain the hydrogel precursor solution.

[0108] In another preferred embodiment, the solvent of the hydrogel precursor solution is selected from the group consisting of water, PBS solution, or combinations thereof.

[0109] In another preferred embodiment, the solvent in step (a1) is selected from the group consisting of water and PBS buffer solution (pH=7.2).

[0110] In a fourth aspect of the invention, a mixture for preparing the hydrogel described in the first aspect of the invention is provided, the mixture comprising the hydrogel precursor solution and coupling agent described in the invention.

[0111] In another preferred embodiment, the viscosity of the mixture is 75-110 mPa·s.

[0112] In another preferred embodiment, the mixture has good injectability.

[0113] In another preferred embodiment, the mixture is injected into the site where tissue adhesion is required, and coupled in situ to obtain the hydrogel described in the first aspect of the present invention.

[0114] In another preferred embodiment, the gelation time of the mixture is within 1 minute, more preferably in the range of 15-40 seconds.

[0115] In a fifth aspect of the invention, a kit for preparing the hydrogel of the first aspect of the invention is provided, the kit comprising:

[0116] (a) A first container, and a hydrogel precursor solution located within the container, the precursor solution comprising the hydrogel precursor solution described in the first aspect of the present invention;

[0117] (b) A second container, and a coupling agent located within the container, the coupling agent comprising the coupling agent described in the first aspect of the present invention.

[0118] In another preferred embodiment, the kit comprises:

[0119] (a) A first container, and a solution of a first polymer and a second polymer located within the container, the solution comprising the first polymer and the second polymer described in the first aspect of the invention;

[0120] (b) A second container, and a third polymer solution located within the container, the solution comprising the third polymer described in the first aspect of the invention;

[0121] (c) A third container, and a coupling agent located within the container, the coupling agent comprising the coupling agent described in the first aspect of the present invention.

[0122] In a sixth aspect of the invention, a medical coating is provided, said medical coating comprising the hydrogel described in the first aspect of the invention.

[0123] In a seventh aspect of the invention, a medical material is provided, said medical material comprising the hydrogel described in the first aspect of the invention.

[0124] In another preferred embodiment, the medical material is selected from the group consisting of: medical tissue sealants, medical hemostatic agents, and medical wound dressings.

[0125] In an eighth aspect of the invention, the use of the hydrogel described in the first aspect of the invention is provided for preparing a medical material for bonding soft tissue wounds and promoting tissue repair and regeneration.

[0126] In a ninth aspect of the invention, a method for bonding a soft tissue wound is provided, the method using the hydrogel described in the first aspect of the invention to bond the soft tissue wound.

[0127] It should be understood that, within the scope of this invention, the above-described technical features of this invention and the technical features specifically described below (such as in the embodiments) can be combined with each other to form new or preferred technical solutions. Due to space limitations, they will not be described in detail here. Attached Figure Description

[0128] Figure 1 The study shows the gelation mechanism. (a) Synthetic routes of aminated polyethylene glycol-polyglycerol sebacic acid and (b) chitosan-gallic acid; (c) Schematic diagram of the tissue adhesion hydrogel preparation mechanism.

[0129] Figure 2 shows the 1H NMR spectra of (a) aminated polyethylene glycol-polysaccharide glycerol and (b) chitosan-gallic acid of the present invention.

[0130] Figure 3 The diagram shows (a) the rheological curve of the gelation process of the tissue-adhesive hydrogel of the present invention; (b) the gelation time diagram; (c) the storage modulus diagram after gelation; and (d) a photograph of the actual gel formed by tilting and inverting a vial.

[0131] Figure 4 The following images show (a) cyclic compression curves, (b) compression strength diagrams, and (c) compression-release images of the tissue-adhesive hydrogel of the present invention.

[0132] Figure 5 The following figures are shown: (a) stretch curve of the tissue-adhesive hydrogel of the present invention; (b) cyclic stretch curve and (c) stretch schematic diagram.

[0133] Figure 6The diagram shows (a) an image of the overlap-shear-tension test of the tissue-bonding hydrogel of the present invention with pigskin; (b) an image of the overlap-shear strength of the tissue-bonding hydrogel of the present invention with commercial fibroin glue and cyanoacrylate over time; and (c) an image of the overlap-shear strength of the hydrogel of the present invention on the surface of pigskin under bending, stretching and twisting.

[0134] Figure 7 The cell viability of the tissue-adhesive hydrogel of the present invention after co-culturing with mouse fibroblasts (L929 cells) is shown. Detailed Implementation

[0135] Combining modern battlefield and clinical needs, and through extensive and in-depth research, the inventors have unexpectedly developed a hydrogel for tissue adhesion that can be formed by injection, addressing the problems of weak adhesion strength and poor adhesion performance in humid and dynamic physiological environments that are commonly used tissue adhesives.

[0136] Specifically, this invention uses aminated polyethylene glycol-polyglycerol sebacic acid as the main matrix material, and incorporates a polyphenol structure inspired by the strong underwater adhesive properties of mussels. This polyphenol structure is mixed with a coupling agent and injected into the wound surface using a syringe for in-situ coupling adhesion, resulting in the tissue adhesive hydrogel described in this invention. Furthermore, the rheological properties, mechanical properties, tensile properties, and adhesive strength of the hydrogel can all be controlled and optimized by changing the ratio of carboxyl groups to EDC. This invention is based on these principles.

[0137] Specifically, the tissue-adhesive hydrogel of this invention utilizes a PEGS-NH2 matrix material with good water solubility and mechanical strength, along with a unique adhesive reinforcing material. After coupling, it can form stable chemical bonds and electrostatic interactions with human tissue, exhibiting excellent viscoelasticity (100% recovery after compression and release, with no significant loss after cyclic compression), biocompatibility, and superior tissue adhesion (adhesion strength to moist tissues can reach up to 48 kPa). It is suitable for moist and dynamic physiological environments. Therefore, the tissue-adhesive hydrogel of this invention can be formed in a short time (within 1 minute) through injection, used for in-situ adhesion of irregular wounds, promoting wound healing and regeneration, and is a tissue adhesive material with broad clinical application prospects.

[0138] the term

[0139] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains.

[0140] As used herein, the terms “containing” or “including (comprise)” can be open-ended, semi-closed, or closed. In other words, the terms also include “consistently made of” or “composed of”.

[0141] As used herein, the term "hydrogel precursor solution" refers to a homogeneous dispersion formed by dissolving the components (including, but not limited to, the first polymer, the second polymer, and the third polymer) in a specific solvent.

[0142] As used herein, the term "coupling component" refers to a component that enables the coupling of components in the precursor solution to form a hydrogel.

[0143] As used herein, the term "coupling agent" refers to a homogeneous dispersion formed when a coupling component is dissolved in a specific solvent.

[0144] As used in this article, the term "dispersion factor" for long-chain polymers refers to the ratio of weight-average molecular weight to number-average molecular weight, D = M. w / M n D≥1. Due to the polydispersity of polymers, their mass is non-uniform. The dispersion coefficient is used to characterize the mass distribution of polymer products; the closer it is to 1, the more uniform the mass distribution.

[0145] As used in this article, the term "grafting rate" refers to the proportion of original groups on the side chains of a molecular chain that are replaced by functional groups, calculated based on the amount of original groups that are replaced on the molecular chain.

[0146] As used herein, the terms “polyethylene glycol-polyglycerol sebacate” and “PEGS” are used interchangeably.

[0147] As used herein, the terms “aminated polyethylene glycol-polysaccharide glycerol”, “aminated PEGS”, and “PEGS-NH2” are used interchangeably.

[0148] As used in this article, the terms "chitosan-gallic acid" and "CS-GA" are used interchangeably.

[0149] As used in this article, the terms “γ-polyglutamic acid” and “γ-PGA” are used interchangeably.

[0150] As used herein, the terms “1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride” and “EDC” are used interchangeably.

[0151] As used herein, the terms “N-hydroxysuccinimide” and “NHS” are used interchangeably.

[0152] As used herein, the terms "phosphate-buffered saline solution" and "PBS" are used interchangeably.

[0153] As used herein, the terms “di(tetrabutylammonium hydroxide) sebacate” and “TBAS” are used interchangeably.

[0154] As used herein, the terms “polyethylene glycol diglycidyl ether” and “PEGDGE” are used interchangeably.

[0155] As used herein, the terms “N-(tert-butyloxycarbonyl)aminoacetic acid” and “BOC-glycine” are used interchangeably.

[0156] As used herein, the terms “N,N’-diisopropylcarbodiimide” and “DIC” are used interchangeably.

[0157] As used herein, the terms “4-dimethylaminopyridine” and “DMAP” are used interchangeably.

[0158] The precursor polymer of the first polymer

[0159] The precursor polymer of the first polymer described in this invention refers to the polymer used to prepare the first polymer of this invention. The polymer exhibits excellent viscoelasticity, as well as good biocompatibility, mechanical strength, and biodegradability.

[0160] The precursor polymer of the first polymer is a copolymer of polyester and polyethylene glycol.

[0161] The main chain of the polyester includes free hydroxyl groups.

[0162] The polyester is an esterification polymer of long-chain diacid and triol.

[0163] The precursor polymer of the first polymer contains structural units as shown in Formula III:

[0164]

[0165] Where c is 1-20 and d is 5-60.

[0166] The precursor polymer of the first polymer is polyethylene glycol-polyglycerol sebacic acid ester, containing structural units as shown in Formula VI:

[0167]

[0168] The PEG block has a molecular weight of 250-2000 Da and a degree of polymerization m of the structure of 5-70.

[0169] First Polymer

[0170] The first polymer mentioned in this invention refers to the first component of the precursor solution used to prepare the hydrogel of this invention.

[0171] The first polymer described in this invention is the main matrix material of the hydrogel of this invention, and it has excellent biocompatibility, biodegradability, and flowability. The side chains of the first polymer molecular chain include a large number of amino groups for coupling.

[0172] The first polymer can bind tightly to human tissues by forming stable chemical bonds or electrostatic interactions.

[0173] The first polymer has a large number of amino groups in its side chains.

[0174] The first polymer is obtained by amylation modification of the precursor polymer of the first polymer.

[0175] The first polymer has one or more of the following characteristics:

[0176] (i) The number average molecular weight is 8,000-18,000 Da, preferably 10,000-16,000 Da, and more preferably 12,000-15,000 Da;

[0177] (ii) The molecular weight distribution coefficient is 1.0 to 1.60, more preferably 1.20 to 1.50;

[0178] (iii) The amino grafting rate is greater than 80%, more preferably greater than 90%, wherein the grafting rate refers to the ratio of H in the original hydroxyl groups in amino-substituted polyethylene glycol-polysaccharide glycerol.

[0179] The first polymer contains structural units as shown in Formula VII:

[0180]

[0181] Where a2 is 1-20 and b2 is 5-60;

[0182] The amino group is grafted here, and the amino group replaces the H of the hydroxyl group on the main chain of PEGS through the grafted chain structure and is attached to the first polymer main chain. The proportion of the group grafted to the molecular chain is greater than 70%.

[0183] The first polymer is an aminated polyethylene glycol-polyglycerol sebacic acid ester, containing structural units as shown in Formula VIII:

[0184]

[0185] Where a3 is 1-20 and b3 is 5-60.

[0186] Second polymer

[0187] The second polymer mentioned in this invention refers to the second component of the precursor solution used to prepare the hydrogel of this invention.

[0188] The second polymer of this invention comprises free amino groups on its side chains for coupling. Furthermore, to improve the adhesion of the hydrogel in humid and dynamic physiological environments, the side chains of the second polymer also include... The grafting rate of the aforementioned groups is 5% to 30%.

[0189] The second polymer is a precursor polymer containing amino groups obtained by... It was obtained through modification.

[0190] The precursor polymer of the second polymer containing amino groups is obtained through... Random copolymers formed by unit polymerization.

[0191] The precursor polymer of the second polymer containing amino groups is chitosan and its derivatives.

[0192] The aforementioned for

[0193] The aforementioned The grafting rate, i.e., the proportion of H in the original amino group that is replaced by this group, is 8% to 20%, more preferably 8% to 12%.

[0194] The number-average molecular weight of the second polymer is 100-150 kDa.

[0195] The second polymer comprises a structure as shown in Formula II:

[0196]

[0197] Among them, the three monomers can be combined arbitrarily to obtain random copolymers;

[0198] l is 45%–80%, m is 5%–30%, and n is 15%–25%. The calculation method for l, m, and n is the corresponding number of repeating units divided by the total number of repeating units.

[0199] In the polymer of formula II, m is 8% to 12%.

[0200] The second polymer used for modification The substances are selected from the following group: gallic acid, myricetin, or combinations thereof.

[0201] The second polymer is chitosan grafted with gallic acid (chitosan-gallic acid), comprising the structure shown in Formula V:

[0202]

[0203] Among them, the three monomers can be combined arbitrarily to obtain random copolymers;

[0204] l1 is 45%–80%, m1 is 5%–30%, and n1 is 15%–25%. l1, m1, and n1 are calculated by dividing the corresponding number of repeating units by the total number of repeating units.

[0205] The gallic acid grafting rate of the chitosan-gallic acid, i.e. the proportion of gallic acid replacing H in the original amino group of chitosan, is 8% to 12%.

[0206] Third polymer

[0207] The third polymer mentioned in this invention refers to the third component of the precursor solution used to prepare the hydrogel of this invention. The molecular chain of the third polymer of this invention includes carboxyl groups for coupling.

[0208] The number-average molecular weight of the third polymer is 200-800 kDa.

[0209] The third polymer is selected from γ-polyglutamic acid, polyaspartic acid, or a combination thereof.

[0210] The third polymer is γ-polyglutamic acid.

[0211] The aforementioned γ-polyglutamic acid is a natural polymer, a large molecular compound formed by D- or L-glutamic acid linked together by amide bonds between α-amino and γ-carboxyl groups. The γ-polyglutamic acid backbone contains a large number of free carboxyl groups. Its structural formula is shown in Formula IX:

[0212]

[0213] The degree of polymerization, n, ranges from 1300 to 5500.

[0214] tissue adhesion hydrogel

[0215] Hydrogels are a class of polymeric materials with a three-dimensional cross-linked network capable of absorbing and retaining large amounts of water. This invention provides a tissue-adhesive hydrogel suitable for humid and dynamic physiological environments.

[0216] The hydrogel is prepared by mixing a hydrogel precursor solution containing two amino-containing polymers and one carboxyl-containing polymer with a coupling agent containing EDC and NHS, and then performing a coupling reaction.

[0217] As used herein, the terms "tissue-adhesive hydrogel", "tissue-adhesive hydrogel of the present invention", "hydrogel of the present invention", and "injectable tissue-adhesive hydrogel" are used interchangeably and refer to a hydrogel material that can be used for tissue adhesion, obtained by injecting a mixture of a hydrogel precursor solution and a coupling agent obtained by the present invention into the desired site via injection and in situ coupling.

[0218] The hydrogel precursor solution of the present invention comprises the first polymer, the second polymer and the third polymer described in the present invention;

[0219] The first polymer and the third polymer are covalently bonded by amide bonds, and the second polymer and the third polymer are covalently bonded by amide bonds.

[0220] The concentration of the first polymer is 10-40% by mass-volume percentage of solute (g) / solvent (mL); the concentration of the second polymer is 0.5-4%; and the concentration of γ-polyglutamic acid is 5-15%.

[0221] The concentration of the first polymer is 20% by mass-volume percentage of solute (g) / solvent (mL); the concentration of the second polymer is 2%; and the concentration of the third polymer is 10%.

[0222] The tissue-adhesive hydrogel described in this invention exhibits excellent tissue adhesion in both moist and dynamic physiological environments.

[0223] The hydrogel has one or more of the following characteristics:

[0224] (1) The compressive strength at 80% compressive strain is in the range of 20-100 kPa;

[0225] (2) It recovers 100% after compression and release, and the hydrogel shows no significant loss after cyclic compression;

[0226] (3) The overlap-shear bond strength of moist tissue is 12-48 kPa.

[0227] Preparation method of tissue bonding hydrogel

[0228] This invention provides a method for preparing a tissue-adhesive hydrogel, the method comprising the steps of:

[0229] (a) Providing a first polymer, a second polymer, a third polymer, a coupling component, and a solvent;

[0230] (b) The first polymer and the second polymer are dissolved in solvents and mixed, and then added to the solution of the third polymer and stirred evenly to obtain a precursor solution of tissue adhesion hydrogel;

[0231] (c) After the above hydrogel precursor solution is mixed evenly with the coupling agent, it is transferred into a syringe and injected to obtain the tissue bonding hydrogel.

[0232] The solvent is PBS solution.

[0233] The method for preparing the first polymer includes the following steps:

[0234] (a1) Sebacic acid and tetrabutylammonium hydroxide were added to 95% ethanol at a molar ratio of 1:2, and the mixture was stirred at 55°C for 30 min. The ethanol and water were removed to obtain the product.

[0235] (b1) Under a nitrogen atmosphere, sebacic acid, polyethylene glycol diglycidyl ether (PEGDGE) and the product obtained in step (a1) were dissolved in anhydrous N,N-dimethylformamide in a molar ratio of 1:1:0.006 and stirred at 100°C for 72 h.

[0236] (c1) Dialysis purification of the product obtained in step (b) yields purified linear polyester PEGS;

[0237] (d1) Under a nitrogen atmosphere, the linear polyester PEGS (based on hydroxyl content) obtained in step (c1) with a molar ratio of 1:1.2:2:0.05, N-(tert-butoxycarbonyl)aminoacetic acid (BOC-glycine), N,N'-diisopropylcarbodiimide (DIC) and 4-dimethylaminopyridine (DMAP) were dissolved in anhydrous dichloromethane and reacted at room temperature with stirring for 24 h.

[0238] (e1) The reaction mixture obtained in step (d1) is filtered, concentrated, and the tert-butyloxycarbonyl group is removed by trifluoroacetic acid. After dialysis purification, the aminated first polymer is obtained.

[0239] Preferably, the molecular weight of the first polymer is 8000-18000 Da, more preferably 10000-16000 Da, and most preferably 12000-15000 Da.

[0240] The method for preparing the second polymer includes the following steps:

[0241] (a2) Dissolve chitosan in 1M hydrochloric acid solution and adjust the pH to 5.5 with 2M sodium hydroxide solution;

[0242] (b2) Under an argon atmosphere, gallic acid, EDC, and NHS are added dropwise to the chitosan solution in step (a2) in a molar ratio of 1.1:1.5:1.5:1 to the chitosan solution (calculated as amino group). The pH of the reaction system is maintained at 4.5-7.0, preferably 5.0-6.5, and more preferably 5.3-5.8. The mixture is continuously stirred during the addition process, and the reaction is continued for 12 hours after the addition is completed.

[0243] (c2) The product of step (b2) is purified by dialysis to obtain the chitosan-gallic acid.

[0244] The dripping rate in step (b2) is 0.5-2 drops / second, more preferably 0.5-1 drops / second.

[0245] Step (b2) is performed in an ice bath at a temperature of -10-5°C, more preferably -5-0°C.

[0246] The main advantages of this invention include:

[0247] 1) The hydrogel described in this invention uses aminated PEGS with excellent viscoelasticity and mechanical strength as the matrix material, and introduces a unique adhesive-enhancing structural material to improve the adhesive strength in humid and dynamic physiological environments.

[0248] 2) The mixture for preparing hydrogels described in this invention can be injected into the desired site to form gels in situ, and the gelation time is between 15-40 seconds, all within 1 minute;

[0249] 3) The hydrogel described in this invention has a certain mechanical strength, and the storage modulus after gelation can reach up to about 4000 Pa. It can maintain its mechanical integrity under large strain (80%) cyclic compression (5 times) without irreversible damage inside, and has excellent fatigue resistance.

[0250] 4) The hydrogel described in this invention has excellent tissue adhesion (the adhesion strength of moist tissue can reach up to 48 kPa), and can be used in moist and dynamic physiological environments.

[0251] 5) The hydrogel described in this invention can achieve the control of rheological properties, tensile properties, adhesive strength, etc. by adjusting the ratio of carboxyl groups in the third polymer to EDC in the coupling agent, so as to meet more types of application requirements;

[0252] 6) The hydrogel described in this invention can be used for in-situ adhesion of irregular wounds, promoting wound healing and regeneration.

[0253] The present invention will be further illustrated below with reference to specific embodiments. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of the invention. Experimental methods in the following embodiments, unless otherwise specified, are generally performed under conventional conditions or as recommended by the manufacturer. Unless otherwise stated, percentages and parts are weight percentages and parts by weight.

[0254] Example 1. Preparation of tissue-adhesive hydrogel

[0255] The synthetic routes of amino-modified PEGS and chitosan-gallic acid, and the mechanism of tissue adhesion hydrogel preparation are shown in the figure below. Figure 1 As shown.

[0256] Example 1.1 Synthesis and purification of amino-modified polyester PEGS

[0257] (a1) Weigh 1.95 g sebacic acid (0.01 mol) and 20 g (0.07 mol) tetrabutylammonium hydroxide (25 wt% aqueous solution) and add them to 100 mL of 95% ethanol. Stir the reaction at 55 °C for 30 min, then remove the ethanol by rotary evaporation at 40 °C, and finally freeze dry to obtain the product di(tetrabutylammonium hydroxide) sebacic acid ester (TBAS).

[0258] (b1) Weigh 20.23 g sebacic acid (0.1 mol), 50.00 g polyethylene glycol diglycidyl ether and 0.41 g of the product TBAS from step (a) under a nitrogen atmosphere. Dissolve the above raw materials in 180 mL of anhydrous N,N-dimethylformamide and stir at 100 °C for 72 h.

[0259] (c1) The product of step (b) was purified by dialysis using a dialysis bag with a molecular weight cutoff of 3500 Da to obtain purified linear polyester PEGS.

[0260] (d1) Under a nitrogen atmosphere, weigh 10.53 g of the linear polyester PEGS obtained in step (c), 6.31 g of N-(tert-butoxycarbonyl)aminoacetic acid, 7.57 g of N,N'-diisopropylcarbodiimide (0.06 mol) and 0.18 g of 4-dimethylaminopyridine (0.001 mol), and dissolve the above raw materials in 150 mL of anhydrous dichloromethane. Stir and react at room temperature for 24 h.

[0261] (e1) The product obtained in step (d) was filtered, concentrated and then the tert-butyloxycarbonyl group was removed by 25 mL of trifluoroacetic acid for 45 min. Then, it was purified by dialysis using a dialysis bag with a molecular weight cutoff of 3500 Da to obtain amino-modified polyester PEGS.

[0262] The obtained amino-modified polyester PEGS had a molecular weight of 8000-18000 Da, a molecular weight distribution coefficient of 1.20-1.50, and an actual amino grafting rate of 90-95%. The proton NMR spectra are shown below. Figure 2a As shown.

[0263] Example 1.2 Synthesis and purification of chitosan-gallic acid

[0264] (a2) Weigh 0.81 g of chitosan and dissolve it in 50 mL of 1 M hydrochloric acid solution, and adjust the pH to 5.5 with 2 M sodium hydroxide solution;

[0265] (b2) Dissolve 0.94 g gallic acid (0.005 mol) in 10 mL of ethanol solution, dissolve 1.44 g EDC (0.007 mol) in 30 mL of water, and dissolve 0.86 g NHS in 10 mL of water for later use;

[0266] (c2) Under the protection of argon atmosphere, the gallic acid solution, EDC solution and NHS solution obtained in step (b2) are added dropwise to the chitosan solution in step (a2) in sequence, and the pH of the reaction system is kept at 5.3-5.8. During the addition process, the mixture is continuously stirred and kept in an ice bath. After the addition is completed, the mixture is stirred and reacted for 12 hours.

[0267] (d2) Dialysis purification of the product of step (c2) yields chitosan-gallic acid.

[0268] The actual grafting rate of gallic acid in the obtained chitosan-gallic acid was 8-12%. The 1H NMR spectrum is shown below. Figure 2b As shown.

[0269] Example 1.3 Preparation of tissue-adhesive hydrogel

[0270] The raw material ratios are shown in Table 1 below. The specific preparation method of the tissue bonding hydrogel includes the following steps:

[0271] (a) Weigh a certain amount of γ-polyglutamic acid and dissolve it in 0.3 mL of ultrapure water, then stir until homogeneous;

[0272] (b) Weigh out a certain amount of amino-modified PEGS and chitosan-gallic acid respectively, dissolve them in 0.2 mL and 0.5 mL of ultrapure water, stir and mix evenly;

[0273] (c) Add the solution from step (b) dropwise to the solution from step (a) while stirring to obtain the hydrogel precursor solution;

[0274] (d) Add a certain amount of EDC (0.7 g / mL) / NHS (0.4 g / mL) aqueous solution to the solution obtained in step (c), stir quickly until homogeneous, and then inject into a gel.

[0275] Table 1. Raw material ratios for preparing tissue-adhesive hydrogels

[0276]

[0277] Under the action of coupling agents EDC / NHS, carboxyl and amino groups undergo amidation to form crosslinking points. The higher the molar ratio of carboxyl groups to EDC in γ-polyglutamic acid (10:1-20:1), the fewer the crosslinking points and the lower the degree of crosslinking. This invention adjusts the degree of crosslinking of the hydrogel by regulating the molar ratio of -COOH to EDC in γ-polyglutamic acid (10:1-20:1), obtaining three hydrogel materials with different degrees of crosslinking. This invention prepares a CS-GA-free hydrogel with a crosslinking degree of 15:1 as a control material to illustrate the influence of polyphenol structure on the properties of the hydrogel described in this invention.

[0278] Example 2. Rheological characterization of tissue-adhesive hydrogels

[0279] To evaluate the injectability of the mixture used to prepare tissue-adhesive hydrogels, this study investigated the changes in storage modulus and loss modulus during hydrogel formation, as well as the gelation time, using a rotational rheometer. The test temperature was 37℃, the frequency was fixed at 10Hz, the strain was fixed at 5%, and the test time was 10 min. Data were recorded to obtain the curves of storage modulus and loss modulus versus time during hydrogel formation. The gelation time and the stable storage modulus of the hydrogel were then analyzed and calculated. The results are as follows: Figure 3 As shown.

[0280] The results showed that the gelation time of all groups of hydrogels was between 15 and 40 seconds, all within 1 minute. Figure 3 (b) and the storage modulus of the tissue-adhesive hydrogel after stable gelation can reach up to about 4000 Pa. Figure 3 (a) illustrates that the hydrogel of this invention can be formed by injection and has a certain mechanical strength.

[0281] The changes in gelation time and storage modulus after stabilization can be seen from (… Figure 3 In samples b and c) of γ-polyglutamic acid (crosslinking degree 10:1-20:1), the crosslinking degree decreased, the gelation time increased, and the storage modulus decreased after stabilization as the ratio of carboxyl groups to EDC in γ-polyglutamic acid continuously decreased. This indicates that the crosslinking degree of the material can be controlled by changing the ratio of carboxyl groups to EDC in γ-polyglutamic acid, thereby controlling the rheological properties and gelation time of the tissue-adhesive hydrogel. Furthermore, the gelation time and storage modulus of samples 2 and 3 were significantly improved compared to sample 4. Samples 1 and 3 had the same crosslinking degree, and their gelation time and storage modulus were not significantly different from those of sample 3.

[0282] Example 3. Characterization of the compressibility properties of tissue-adhesive hydrogels

[0283] To evaluate the mechanical properties and fatigue resistance of tissue-bonding hydrogels, this study conducted cyclic compression tests on the hydrogels using a universal tensile testing machine. The maximum strain was fixed at 80%, and the number of cycles was 5. Data were recorded, and cyclic compression curves were plotted to analyze and evaluate the stability of the hydrogels under cyclic compression. The results are as follows: Figure 4 As shown.

[0284] from Figure 4 As can be seen from 'a', the cyclic compression curves of the hydrogel basically overlap, indicating that the hydrogel can maintain its mechanical integrity after 5 cycles of compression at a relatively large strain (80%), and the maximum compressive strength can reach 100 kPa. Figure 4 (a, b in the text). Furthermore, it exhibits 100% recovery after compression and release, no significant loss of the hydrogel after cyclic compression, and no irreversible internal damage, demonstrating excellent fatigue resistance. Figure 4 The 'c' indicates that the hydrogel of this invention has good resilience.

[0285] Furthermore, the compressive strength of the hydrogel at the point of maximum strain gradually increases with increasing crosslinking degree (20:1-10:1). Figure 4 b) In other words, the compressibility of tissue-adhesive hydrogels can be controlled by changing the degree of crosslinking.

[0286] Example 5. Characterization of the tensile properties of tissue-adhesive hydrogels

[0287] To evaluate the tensile properties of tissue-bonding hydrogels, this study used a universal tensile testing machine to conduct tensile and cyclic tensile tests on the hydrogels. The tensile speed was fixed at 10%, and the maximum strain in the cyclic tensile tests was fixed at 100%, with 10 cycles. Data were recorded, and tensile and cyclic tensile curves were plotted to analyze and evaluate the elongation at break and stability of the hydrogels under cyclic tensile conditions. The results are as follows: Figure 5 As shown.

[0288] from Figure 5 As can be seen from 'a', the elongation at break of the hydrogel can reach 250%-420%, indicating that the hydrogel has good tensile properties. From... Figure 5 As can be seen from b, the cyclic tensile curves of the hydrogel basically overlap, indicating that the hydrogel can maintain its mechanical integrity after 10 cycles of cyclic tensile stress at a large strain (100%), without internal structural damage, and has excellent fatigue resistance. Figure 5 The 'c' indicates that the hydrogel has good tensile properties.

[0289] Example 6. Characterization of the adhesive strength of tissue-adhesive hydrogels to moist tissues

[0290] To evaluate the adhesion performance of the tissue-adhesive hydrogel to moist tissue (pigskin soaked in PBS), this study investigated the adhesive strength of the hydrogel using an overlap-shear tensile test. Each piece of pigskin was 6 cm long and 2.5 cm wide, with an overlap of 2.5 x 1 cm. The pigskin was soaked in PBS before being bonded with the hydrogel to simulate a moist physiological environment in vivo. The tensile rate was 10 mm / min. The results are as follows: Figure 6 As shown.

[0291] The results showed that the adhesive strength of the tissue-adhesive hydrogels in all groups was superior to that of the commercially available fibrin glue in the control group, with the highest reaching 48 kPa. Figure 6 While the adhesive strength of (b, c) is not significantly superior to that of cyanoacrylate adhesives, cyanoacrylate tissue adhesives harden after curing, making them unsuitable for dynamic environments, and their degradation products are somewhat toxic. This indicates that the hydrogel of the present invention has excellent adhesive properties to moist tissues. The hydrogel with a molar ratio of γ-polyglutamic acid carboxyl groups to EDC of 15:1 exhibits the highest adhesive strength, comparable to commercially available cyanoacrylate adhesives.

[0292] It is worth noting that samples 2-4, obtained by adding chitosan-gallic acid, showed a significant improvement in adhesion to moist tissues compared to sample 1, obtained without the addition of this material. Figure 6 c) indicates that polyphenol structures can act as adhesive reinforcing agents, significantly improving the adhesive strength of damp tissues.

[0293] from Figure 6 As can be seen from 'd', the tissue adhesion hydrogel can adhere to the surface of pigskin and remain attached even when the pigskin is bent, stretched, and twisted. This indicates that the hydrogel of the present invention is suitable for dynamic physiological environments.

[0294] Example 7. Cell compatibility characterization of tissue-adhesive hydrogels

[0295] To evaluate the cytocompatibility of tissue-adhesive hydrogels, this study investigated their cytotoxicity at 1, 3, and 7 days by co-culturing mouse fibroblasts (L929) with the hydrogel.

[0296] from Figure 7 It can be seen that all groups of tissue-adhesive hydrogels showed no significant toxicity to L929 cells compared to the control (TCP) at 1d, 3d, and 7d after co-culturing with L929 cells, indicating that the tissue-adhesive hydrogels described in this invention have good cell compatibility.

[0297] In summary, the high-efficiency tissue adhesive hydrogel of this invention has a short gelation time, can be rapidly gelled via injection, exhibits excellent tissue adhesion strength, good cell compatibility, and adaptability to moist and dynamic physiological environments. Furthermore, the rheological properties, gelation time, mechanical properties, and adhesive strength of the hydrogel can be controlled and optimized by adjusting the ratio of carboxyl groups to EDC. The sample with a carboxyl group to EDC ratio of 15:1 exhibits the highest adhesive strength to moist tissues, a high storage modulus, and a short gelation time. Therefore, the hydrogel of this invention can be used for in-situ adhesion of irregular wounds, promoting wound healing and regeneration, and is a tissue adhesive material with promising applications in modern battlefields and clinical settings.

[0298] All documents mentioned in this invention are incorporated herein by reference as if each document were individually incorporated by reference. Furthermore, it should be understood that after reading the foregoing teachings of this invention, those skilled in the art can make various alterations or modifications to this invention, and these equivalent forms also fall within the scope defined by the appended claims.

Claims

1. A tissue-adhesive hydrogel, characterized in that, The tissue-adhesive hydrogel is formed by coupling a hydrogel precursor solution with a coupling agent; The hydrogel precursor solution comprises a first polymer, a second polymer, and a third polymer. The first polymer is an aminated polyethylene glycol-polyglycerol sebacic acid ester, which contains structural units as shown in Formula I: ; I a is 1-20, b is 5-60; Y is independently selected from the following groups: H, Furthermore, on average, each structural unit contains at least one ; The side chains of the second polymer contain amino groups and... The second polymer is a functionalized chitosan with a number-average molecular weight of 100-150 kDa, comprising the structure shown in Formula II: II Among them, the three monomers can be combined arbitrarily to obtain random copolymers; l is 45-80%, m is 5-30%, and n is 15%-25%. The calculation method for l, m, and n is the corresponding number of repeating units divided by the total number of repeating units. The side chain of the third polymer contains a carboxyl group; the third polymer is selected from the group consisting of γ-polyglutamic acid, polyaspartic acid, or combinations thereof; The mass ratio of the first polymer to the second polymer is 5~50:1; and / or The mass ratio of the first polymer to the third polymer is 1~8:1; and / or The mass ratio of the second polymer to the third polymer is 1:1 to 10; The coupling agent comprises 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride (EDC) and N-hydroxysuccinimide (NHS). The molar ratio of the carboxyl group in the third polymer side chain to the EDC in the coupling agent is 5~30:

1.

2. The tissue-adhesive hydrogel as described in claim 1, characterized in that, The first polymer contains structural units as shown in Formula IV: IV In the formula, a1 is 1-20, b1 is 5-60; Z is independently selected from the following groups: H, Furthermore, each structural unit typically contains at least 1 to 1.4 [units / elements]. .

3. The tissue-adhesive hydrogel as described in claim 1, characterized in that, The first polymer and the third polymer are covalently bonded by amide bonds, and the second polymer and the third polymer are covalently bonded by amide bonds.

4. The tissue-adhesive hydrogel as described in claim 1, characterized in that, The first polymer is obtained by amylation modification of the precursor polymer of the first polymer. The precursor polymer of the first polymer is polyethylene glycol-polyglycerol sebacic acid, which contains structural units as shown in Formula III: III Where c is 1-20 and d is 5-60.

5. The tissue-adhesive hydrogel as described in claim 1, characterized in that, The amino grafting rate of the first polymer, i.e., the ratio of H in the original hydroxyl groups in the amino-substituted polyethylene glycol-polysaccharide glycerol, is greater than 70%.

6. The tissue-adhesive hydrogel as described in claim 1, characterized in that, The first polymer is the main matrix material and has one or more of the following characteristics: (a) Number-average molecular weight of 5000-50000 Da; (b) The molecular weight distribution coefficient is 1.0 to 1.60; (c) On average, a structural unit contains at least 1.4 .

7. The tissue-adhesive hydrogel as described in claim 1, characterized in that, The aforementioned The grafting rate, that is, the proportion of H in the original amino group that is replaced by this group, is 5% to 30%.

8. The tissue-adhesive hydrogel as described in claim 1, characterized in that, The second polymer is a precursor polymer containing amino groups obtained by... Obtained through modification The precursor polymer of the second polymer containing amino groups is obtained through... and Random copolymers formed by unit polymerization.

9. The tissue-adhesive hydrogel as described in claim 1, characterized in that, The aforementioned for .

10. The tissue-adhesive hydrogel as described in claim 1, characterized in that, The second polymer used for modification The substances are selected from the following group: gallic acid, myricetin, or combinations thereof.

11. The tissue-adhesive hydrogel as described in claim 1, characterized in that, The second polymer is chitosan grafted with gallic acid (chitosan-gallic acid), comprising a structure as shown in Formula V: V Among them, the three monomers can be combined arbitrarily to obtain random copolymers; l1 is 45-80%, m1 is 5-30%, and n1 is 15%-25%. l1, m1, and n1 are calculated by dividing the corresponding number of repeating units by the total number of repeating units.

12. The tissue-adhesive hydrogel as described in claim 1, characterized in that, The number-average molecular weight of the third polymer is 200-800 kDa.

13. The tissue-adhesive hydrogel as described in claim 1, characterized in that, The concentration of the first polymer is 10-40% by mass-volume percentage of solute (g) / solvent (mL); the concentration of the second polymer is 0.5-4%; and the concentration of γ-polyglutamic acid is 5-15%.

14. The tissue-adhesive hydrogel as described in claim 1, characterized in that, The hydrogel has one or more of the following characteristics: (1) The compressive strength at 80% compressive strain is 20-100 kPa; (2) 100% recovery after compression and release, and no significant loss of hydrogel after cyclic compression; (3) The elongation at break reaches 200%-450%; (4) The overlap-shear bond strength for moist tissues is 10-60 kPa; (5) The bonded wet tissue does not fall off after bending, stretching and twisting.

15. The tissue-adhesive hydrogel as described in claim 14, characterized in that, The hydrogel has one or more of the following characteristics: (1) Elongation at break is 250%-420%; (2) The overlap-shear bond strength of the wet tissue is 12-48 kPa.

16. The method for preparing the tissue-adhesive hydrogel according to any one of claims 1-15, characterized in that, The preparation method includes: In the presence of a coupling agent, the hydrogel precursor solution of claim 1 undergoes a coupling reaction to form the hydrogel.

17. A mixture for forming the tissue-adhesive hydrogel of claim 1, characterized in that, The mixture comprises the hydrogel precursor solution of claim 1 and the coupling agent; The viscosity of the mixture is 75-110 mPa·s, which meets the requirements for injection.

18. The mixture as claimed in claim 17, characterized in that, The gelation time of the mixture is within 1 minute.

19. The mixture as claimed in claim 18, characterized in that, The gelation time of the mixture is in the range of 15-40 seconds.

20. A kit for preparing the tissue-adhesive hydrogel of claim 1, the kit comprising: (a) A first container, and a hydrogel precursor solution located within the container, the hydrogel precursor solution comprising the hydrogel precursor solution of claim 1; (b) A second container, and a coupling agent located within the container, the coupling agent comprising the coupling agent of claim 1.

21. The use of the hydrogel as described in claim 1, characterized in that, This is used to prepare a medical material for use in the adhesion of soft tissue wounds, promoting tissue repair and regeneration.

22. A medical coating comprising the hydrogel of claim 1.

Citation Information

Patent Citations

  • Viscous hydrogel as well as preparation and application thereof

    CN108853597A

  • Preparation method of multifunctional double-component hydrogel tissue adhesive

    CN110180017A